Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/app10248928
|View full text |Cite
|
Sign up to set email alerts
|

Free and Bound Volatile Aroma Compounds of ´Maraština´ Grapes as Influenced by Dehydration Techniques

Abstract: Dehydration or drying of grapes is one of the most important steps in the production of Croatian traditional dessert wine Prošek. The natural sun drying of grapes is the traditionally used method in Prošek production. Alternative methods, such as dehydration under controlled conditions, have been studied as safer and faster methods than the traditional sun drying but without precise knowledge of the effect on volatile compounds. The objective of this work was to study how dehydration of grapes carried out in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…trans-8-hydroxy linalool n.d. Floral [43] cis-8-hydroxy linalool n.d. Floral [43] Norisoprenoids β-damascone 0.09 [44] Fruity-flowery, exotic-spicy [52] β-damascenone 0.05 [44] Apple, rose, honey [44] α-pinene n.d. Woody, resinous [53] α-ionone 2.6 [54] Violets, berry [55] α-ionol n.d. Floral and woody [55] Aliphatic alcohols 1-hexanol 8000 [44] Resin, green (cut grass) [44] trans-3-hexen-1-ol 1000 [54] Grassy green, earthy [56] cis-3-hexen-1-ol 400 [44] Lettuce-like, green, grass [44] Benzenoid benzaldehyde 2000 [57] Bitter almond [57] methyl salicylate 50 [58] Mint-like [43] Vanillins zingerone n.d. Toasty, dry fruit Phenols guaiacol 10 [44] Smoke, sweet, medicine [44] According to the quali-quantitative results of the volatile fraction, the main monoterpenes (geraniol, linalool, diendiol I, diendiol II, geranic acid, trans-8-hydroxy linalool, and cis-8-hydroxy linalool) characteristic of Moscato Giallo grapes and wine were further investigated by means of isotopic analysis. For the stable isotope ratio analysis, free and bound VOCs were merged, as reported above.…”
Section: Quali-quantitative Analysis By Gc-ms/msmentioning
confidence: 99%
“…trans-8-hydroxy linalool n.d. Floral [43] cis-8-hydroxy linalool n.d. Floral [43] Norisoprenoids β-damascone 0.09 [44] Fruity-flowery, exotic-spicy [52] β-damascenone 0.05 [44] Apple, rose, honey [44] α-pinene n.d. Woody, resinous [53] α-ionone 2.6 [54] Violets, berry [55] α-ionol n.d. Floral and woody [55] Aliphatic alcohols 1-hexanol 8000 [44] Resin, green (cut grass) [44] trans-3-hexen-1-ol 1000 [54] Grassy green, earthy [56] cis-3-hexen-1-ol 400 [44] Lettuce-like, green, grass [44] Benzenoid benzaldehyde 2000 [57] Bitter almond [57] methyl salicylate 50 [58] Mint-like [43] Vanillins zingerone n.d. Toasty, dry fruit Phenols guaiacol 10 [44] Smoke, sweet, medicine [44] According to the quali-quantitative results of the volatile fraction, the main monoterpenes (geraniol, linalool, diendiol I, diendiol II, geranic acid, trans-8-hydroxy linalool, and cis-8-hydroxy linalool) characteristic of Moscato Giallo grapes and wine were further investigated by means of isotopic analysis. For the stable isotope ratio analysis, free and bound VOCs were merged, as reported above.…”
Section: Quali-quantitative Analysis By Gc-ms/msmentioning
confidence: 99%
“…Anise is a plant native to the Middle East that has been used since ancient Egypt, and its major volatile compound is anethol, which is responsible for aniseed's fragrant characteristics [29,48,49]. Anethol was found in very high concentration in Limnos samples, followed by aniseed Muscat samples from Macedonia, while estragole, menthol, 4-anisaldehyde, p-anisaldehyde diethyl acetal, alpha-himachalene, gamma- o-Cymene [34,40,41], alpha-pinene [42][43][44], beta-myrcene [21], D-limonene [21,45], ylangene [18,29], alpha-cedrene [46] and alpha-terpinene [14,29] were detected mostly in Muscat, Muscat of Alexandria and Merlot wines, grape musts, and spirits, as they are characteristic metabolites of these cultivar grapes; however, in this study, their concentration was found to be over 50-fold higher in some Muscat grape marc spirit samples originated from Macedonia. Caryophyllene has been previously found in Cabernet Sauvignon berries [47], while Garcia-Martin et al [35] found terpenols in orujo samples and Giannetti et al [14] and Lukic et al [19] detected terpenes, such as alpha-terpinene, p-cymene, alpha-cubebene, and alpha-calacorene in several European spirit samples.…”
Section: Identification Of Volatile Metabolites In Analyzed Grape Mar...mentioning
confidence: 99%
“…After the characterization and calibration of the system, said system is used to analyze the substances. The sample holder is cleaned using Propanol [67,68], followed by a spray of nitrogen gas, in order to ensure non-presence of any contamination. This is essential for reliable and accurate measurements, and must be done before the commencement of each experimentation with a different substance.…”
Section: Measurements With Substancesmentioning
confidence: 99%